Whistleblowing disclosure policy and cost of equity in ASEAN 5 publicly listed companies: a new establishment of regional whistleblowing disclosure scoring index - Mohd Fairuz Md. Salleh,; Wan Sallha Yusoff,; Norida Basnan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Healthy corporate governance is necessary for attracting investor participation and alleviating corruption. Akin to other developing nations, two major challenges arise. First, Increasing foreign direct investments (FDIs) and second, controlling corruption are faced by all countries in the Association of South East Asian Nations (ASEAN) for their economic development. Phenomenal practices of whistleblowing policies in developed countries, especially in Europe and the US, have become crucial elements for modern corporate governance. Such practices also play important roles in detecting fraud and enhancing FDI and GDP growth. The aims of this study are twofold: to uncover the extent of the effects of whistleblowing disclosure quality on cost of equity (COE) and to propose whistleblowing disclosure scoring index as a new mechanism to integrate whistleblowing disclosure policy in the ASEAN region. Furthermore, a proposal for promulgating a comprehensive whistleblowing policy with inclusive internal and external programmes, which are necessary for establishing strong corporate governance, is presented. Empirical results confirm that whistleblowing disclosure quality has a significant negative relationship with COE. Our finding suggests that a uniform and comprehensive whistleblowing policy is needed to strengthen the best practices of ASEAN Corporate Governance Codes.